2005
DOI: 10.1159/000088760
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in the Expression of Tyrosine Hydroxylase mRNA in Neurosecretory Neurons of the Human Paraventricular and Supraoptic Nuclei: Positive Correlation with Vasopressin mRNA

Abstract: Previous studies indicated that in the human paraventricular nucleus (PVN) and in the supraoptic nucleus (SON) tyrosine hydroxylase (TH) – the first and rate-limiting enzyme in catecholamine synthesis – is localized mainly in magnocellular neurosecretory neurons. Individual differences were observed among control subjects in number and distribution of TH-immunoreactive (IR) perikarya, indicating that antemortem factors may regulate TH expression. Since a large number of TH-IR perikarya were observed in subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 118 publications
(86 reference statements)
0
12
0
Order By: Relevance
“…Moreover, discrepancy between TH mRNA and protein level might appear also due to different stability, transcription rate, post-transcriptional modifications by RNA interference or epigenetic regulation of TH and PNMT expression in adipocytes during various time intervals of stress exposure, similarly as described in other cells and tissues (Lenartowski and Goc, 2011; Nakashima et al, 2007; Panayotacopoulou et al, 2005). …”
Section: Discussionmentioning
confidence: 96%
“…Moreover, discrepancy between TH mRNA and protein level might appear also due to different stability, transcription rate, post-transcriptional modifications by RNA interference or epigenetic regulation of TH and PNMT expression in adipocytes during various time intervals of stress exposure, similarly as described in other cells and tissues (Lenartowski and Goc, 2011; Nakashima et al, 2007; Panayotacopoulou et al, 2005). …”
Section: Discussionmentioning
confidence: 96%
“…Co-expression of tyrosine hydroxylase (TH), the first rate-limiting enzyme of catecholamine synthesis, under functional stimulation or deafferentation of VP neurons, appears to be among the most intriguing observations (Kiss and Mezey 1986;Abramova et al 2000Abramova et al , 2002Panayotacopoulou et al 2005). TH, as Fos (Pirnik and Kiss 2005), is considered as a marker of the VP neuron activation and plasticity, although the functional role and regulation of TH remain uncertain (Marsais and Calas 1999;Kontostavlaki et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the above quoted study by Mai et al (), these authors did not find a reduction in neurophysin staining in the supraoptic nucleus of the schizophrenic patients compared to controls. Further, in a combined immunohistochemical and in situ hybridization study of vasopressin in the supraoptic nucleus, it was not possible to detect any difference in vasopressin expression and vasopressin mRNA expression in this nucleus in schizophrenic patients compared to controls (Panayotacopoulou, Malidelis, Heerikhuize, Unmehopa, & Swaab, ).…”
Section: Discussionmentioning
confidence: 96%
“…This problem has also been investigated in human postmortem hypothalamus. Thus, a combined immunohistochemical and in situ hybridization study showed that the number of cell bodies immunoreactive to tyrosine hydroxylase, the rate‐limiting enzyme in the catecholamine synthesis, and mRNA encoding tyrosine hydroxylase was well correlated (Panayotacopoulou et al, ). We have in our material of the brains of deceased with schizophrenia investigated the expression of proteins by use of antibodies against both vasopressin and neurophysin.…”
Section: Discussionmentioning
confidence: 99%